2000
DOI: 10.2165/00003495-200059040-00007
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid

Abstract: Linezolid is an oxazolidinone antibacterial agent that acts by inhibiting the initiation of bacterial protein synthesis. Cross-resistance between linezolid and other inhibitors of protein synthesis has not been demonstrated. Linezolid has a wide spectrum of activity against gram-positive organisms including methicillin-resistant staphylococci, penicillin-resistant pneumococci and vancomycin-resistant Enterococcus faecalis and E. faecium. Anerobes such as Clostridium spp., Peptostreptococcus spp. and Prevotella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
1
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(182 citation statements)
references
References 29 publications
4
164
1
10
Order By: Relevance
“…administration, continuous monitoring of levels and occasionally, patients experience some unacceptable side effects. Linezolid, on the other hand, is also available in oral form [6]. This drug is rapidly and completely absorbed after oral administration, with a mean bioavailability of approximately 100% and it does not require continuous monitoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…administration, continuous monitoring of levels and occasionally, patients experience some unacceptable side effects. Linezolid, on the other hand, is also available in oral form [6]. This drug is rapidly and completely absorbed after oral administration, with a mean bioavailability of approximately 100% and it does not require continuous monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Linezolid is the first drug among a new class of antibiotics, the oxazolidiones. This drug, unlike other protein synthesis microbiology Section inhibitors, acts early in translocation by disrupting the interaction of formyl methionine t-RNA with the 50s ribosomal subunit during initiation of pre initiation complex [6].Its spectrum includes medically important gram-positive bacteria such as methicillinsusceptible Staphylococcus aureus (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Linezolid is one of the investigational agents. 39,40 In this study linezolid showed excellent activity against multiantibiotic-resistant enterococci. Clinical efficacy and safety studies are needed to determine its real utility.…”
Section: Discussionmentioning
confidence: 71%
“…erreicht und die Halbwertszeit (t1/2) beträgt etwa 5 Stunden (Tab. 2) [6]. Über 65% der Dosis werden als Metaboliten renal ausgeschieden [7].…”
Section: Pharmakokinetik / Pharmakodynamikunclassified